Further documents from the history of economic thought - Samuels, Warren J., 1933- (Research in the history of economic thought and methodology ;, 2007)
Volume 25-C commences a series of class notes taken at Northwestern and Chicago during the period 1964-1967. The notes from courses at Northwestern are Robert Clower's course on economic theory,and Frank Fetter's course on monetary institutions and policies. The notes from Chicago include George Stigler's course on industrial organization, Merton Miller's course on corporate finance, and Daniel Orr's course on the theory of the firm. Also included are Warren Samuels notes from James Earley's courses on economic theory and on money, income and price, given at Wisconsin during 1954-1955; and Samuels' notes from a faculty seminar on myth, theology and society given by Robert T. Anderson at Michigan State University in 1974. The series presents review essays, multiple reviews and mini symposia on new-works in this field. The volumes are broad in scope, and the series fills a substantial gap in this field.